2016
DOI: 10.1016/j.celrep.2016.08.060
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming by De-bookmarking the Somatic Transcriptional Program through Targeting of BET Bromodomains

Abstract: One critical event in reprogramming to pluripotency is erasure of the somatic transcriptional program of starting cells. Here, we present the proof of principle of a strategy for reprogramming to pluripotency facilitated by small molecules that interfere with the somatic transcriptional memory. We show that mild chemical targeting of the acetyllysine-binding pockets of the BET bromodomains, the transcriptional bookmarking domains, robustly enhances reprogramming. Furthermore, we show that chemical targeting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 39 publications
5
30
1
Order By: Relevance
“…In contrast, our results showed that JQ1 caused the loss of cellular extensions in NDs, followed by rounding of cells. These results are similar to previously reported morphological changes observed with other JQ1 sensitive cells, including pancreatic stellate cells and human foreskin fibroblasts [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, our results showed that JQ1 caused the loss of cellular extensions in NDs, followed by rounding of cells. These results are similar to previously reported morphological changes observed with other JQ1 sensitive cells, including pancreatic stellate cells and human foreskin fibroblasts [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…In an effort to improve the efficiency of this process, we screened a collection of seven chemical compounds that were previously shown to promote reprogramming of fibroblasts to induced pluripotent stem cells (Table S1) (Brady et al., 2013, Dutta et al., 2011, Esteban et al., 2010, Ichida et al., 2014, Li et al., 2012, Maherali and Hochedlinger, 2009, Shao et al., 2016). Mouse embryonic fibroblasts (MEFs) were isolated from transgenic mice that express GFP under the control of the cardiac α-myosin heavy chain promoter (αMHC-GFP), and reprogramming was induced by transducing the cells with retroviruses encoding for GHMT.…”
Section: Resultsmentioning
confidence: 99%
“…We used two types of cutoffs for DESeq2 read counts for genes considered expressed, mean read count and individual read count cutoff. In DESeq2 normalization, we previously used a mean normalized read counts of 50 for the cell type in question as a cutoff for a gene to be considered active [7,8]. This cutoff is supported by our current data (table S1).…”
Section: Read Count Cutoff Of Deseq2 Data For Expressed Genementioning
confidence: 56%
“…Conversion of fibroblasts into iPSCs involves dramatic changes in cell morphology and establishes a unique cellular colony characteristic of PSC culture. In fact, high quality iPS cell lines can be established by selecting colonies with the characteristic cell and colony morphology without a reporter [7,8,20], and automatic imaging system can be used for identification of high quality iPSC colonies [21]. GO analyses of reprogramome reveal that 22 and 23 such GO terms are associated with the downreprogramome and upreprogramome, respectively (Table S6).…”
Section: Profiling and Quantification Of Reprogramming In Cell Morphomentioning
confidence: 99%
See 1 more Smart Citation